GE-08: evaluation of basal heave failure for wide excavation - Ee, Peng Peng (2014)
Braced excavation is widely used in construction projects nowadays. There are different failure modes and the most common mode is basal heave failure. To prevent basal heave failure, the minimum factor of safety must be met. To calculate the factor of safety, one can either use conventional methods like Terzaghi’s Method or Finite Element Method. However, it must be noted that Terzaghi’s Method does not take into consideration the depth of embedment of the wall, the thickness of the clay layer beneath the excavation and the stiffness of the wall. In this project, the Finite Element Method (FEM) program Plaxis 2D was used to determine the factor of safety. The parameters that were investigated were the depth of wall embedment, the thickness of the clay layer, and the stiffness of the wall. The results indicate that the depth of wall embedment, the thickness of the clay layer and the stiffness of the wall do have a considerable effect on the factor of safety obtained by Finite Element Method. In addition, the conventional methods were found to underestimate the factor of safety. The disadvantage of the Finite Element Method is that it is more tedious and time-consuming.